1998
DOI: 10.1159/000008611
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Lymphorrhea by Means of Fibrin Glue after Axillary Lymphadenectomy in Breast Cancer: Prospective Randomized Trial

Abstract: A prospective randomized trial was carried out to evaluate the efficacy of fibrin glue in preventing lymphorrhea after axillary lymphadenectomy in breast cancer. One hundred and eight breast cancer patients, operated on by two senior surgeons, were randomized into two groups: group 1 (n = 58) without fibrin glue and group 2 (n = 50) with 2 ml of fibrin glue applied to the axillary dissection area at the end of the lymphadenectomy procedure. Early postoperative morbidity was 2/58 and 0/50 in groups 1 and 2, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 9 publications
2
62
0
1
Order By: Relevance
“…The exact etiology of seroma formation remains controversial. Several interventions have been reported with the aim of reducing seroma formation including the use of ultrasound scissors in performing lymphadenectomy [13], buttress suture [14], fibrin glue [15], fibrin sealant [16], bovine thrombin application [17], and altering surgical technique to close dead space [18]. However, it has been suggested that although the use of these interventions might reduce the risk of seroma formation, further studies are needed to verify the real impact on long-term morbidity of such techniques [19].…”
Section: Discussionmentioning
confidence: 99%
“…The exact etiology of seroma formation remains controversial. Several interventions have been reported with the aim of reducing seroma formation including the use of ultrasound scissors in performing lymphadenectomy [13], buttress suture [14], fibrin glue [15], fibrin sealant [16], bovine thrombin application [17], and altering surgical technique to close dead space [18]. However, it has been suggested that although the use of these interventions might reduce the risk of seroma formation, further studies are needed to verify the real impact on long-term morbidity of such techniques [19].…”
Section: Discussionmentioning
confidence: 99%
“…26 Bonjar et al documented that the cumulative aspirate volumes for seromas in the drain group were significantly greater in control group than in the fibrin glue group. 27 Cumulative seroma volume in fibrin glue and control groups was 110 and 210 mL, respectively (P = 0.0015). Gilly L et al concluded that the use of fibrin glue in axillary lymphadenectomy for breast cancer leads to a significant reduction in postoperative drainage volume, hospital stay period but does not affect delayed seroma formation.…”
Section: The Statistical Analysis Of Received Pre-and Postoperative Dmentioning
confidence: 92%
“…Fibrin sealant has also been shown to be effective in reducing seroma formation in animal models of mastectomy and in reducing drainage after axillary dissection [15,16]. However, in recent studies, the reduction in drainage amount has been shown to depend on the concentration of fibrinogen and thrombin in the fibrin sealant [17][18][19]. Excessively high concentrations of either component can be disadvantageous.…”
Section: Discussionmentioning
confidence: 99%